2014
DOI: 10.1590/s1517-83822014000200012
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol production from agricultural wastes using Sacchromyces cervisae

Abstract: The main objective of this study was production of ethanol from three lignocellulosic biomasses like sugarcane bagasse, rice straw and wheat straw by Sacchromyces cervisae. All the three substrates were ground to powder form (2 mm) and pretreated with 3%H2O2 + 2% NaOH followed by steaming at 130 °C for 60 min. These substrates were hydrolyzed by commercial cellulase enzyme. The whole fermentation process was carried out in 500 mL Erlenmeyer flask under anaerobic conditions in submerged fermentation at 30 °C fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 32 publications
2
15
1
Order By: Relevance
“…Cellulose content in KG was measured by method described by Krishna and Ranjhan [21], lignin and delignification was measured as described by Irfan et al [22]. The saccharified biomass was passed through four layers of muslin cloth and washed with water to remove the microbial biomass and then dried overnight at 1058C to estimate the dry weight of the substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Cellulose content in KG was measured by method described by Krishna and Ranjhan [21], lignin and delignification was measured as described by Irfan et al [22]. The saccharified biomass was passed through four layers of muslin cloth and washed with water to remove the microbial biomass and then dried overnight at 1058C to estimate the dry weight of the substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Hemicellulose was estimated by method as described by Van soest and coworker . Delignification was calculated using following formula . Delignification true(%true) = LnormaluLnormaltLnormalu×100 where L u = Lignin contents/g of untreated dry biomass and L t = Lignin contents/g of treated dry biomass.…”
Section: Methodsmentioning
confidence: 99%
“…Hemicellulose was estimated by method as described by Van soest and coworker [14]. Delignification was calculated using following formula [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the peak at 1246 cm -1 (Wang et al, 2004), the indicator of aromatic C=O stretching out of lignin, decreased in intensity in the combination pretreatment RS. The carbohydrate-related peaks at 1161 cm -1 was assigned to the C-O-C vibration in cellulose and hemicellulose(Irfan et al, 2014), which also decreased in intensity after combination pretreatment, These results indicated that the lignin, cellulose and/or hemicellulose in RS were modified and even degraded by combination pretreatment.…”
mentioning
confidence: 78%